PEMBELAJARAN PENDIDIKAN JASMANI DI MASA PANDEMI COVID-19 MENGGUNAKAN APLIKASI GOOGLE CLASSROOM - Syavira Aulia; Desty Endra Wati Subroto; Dewi Noviana; M Ibnu Kamil (CV. Denasya Smart Publisher, 2025)
During the Covid-19 pandemic, PJOK (Physical Sports and Health Education) learning cannot be carried out in all places because it must follow government regulations regarding maintaining distance and avoiding crowds. This causes various obstacles in its implementation in the field. This research was conducted using a literature review method using sources from Google Scholar. Keywords used include